Be quiet, Mike! - Patricelli, Leslie (Candlewick Press, 2011)
Monkey Mike is reprimanded for making noise when he taps pencils and clangs trash cans until he sees a drum set in the music store and puts his hands-on talents to work in a most impressive way.